Social Support Pada Achievement Anak Jalanan - Husnul Khotimah; Taufiqurrahman Taufiqurrahman; Muhammad Untung Manara (Universitas Nusa Cendana, 2019)
This research aimed to know the contribution of social support to the achievement of street children that referred to the achievements that had been achieved and the failures that had been experienced. This study used the achievement open-ended questionnaire developed by Kim and adapted by the centre for the indigenous and cultural psychology, Gadjah Mada University. The study used categorical qualitative analysis and descriptive quantitative analysis. The respondents of this study were street children in Malang which are 135 subjects who were sampled bysnowball sampling technique. The result showed that social support as an external factor had a smaller contribution than internal factors, both to the achievements and the failures of street children. This study also showed the family as the most important role both in the achievement and the failures of the street children.